Evaluating the Role of Business Policy in Sustaining Competitive Advantage: A Case Study in Manufacturing Industry - Mahmuddin, Mahmuddin; Tahir, Sumiati; Nurfadillah T, Rezki; Pahrul, Pahrul (International Journal of Business, Law, and Education, 2025)
This study evaluates the role of business policy in sustaining competitive advantage within the manufacturing industry by examining three key strategic dimensions: Policy Design, Policy Implementation, and Innovation & Sustainability. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), the study collected data from 120 manufacturing employees and assessed the measurement and structural models through reliability testing, validity assessments, and bootstrapping procedures. The results indicate that all constructs demonstrated strong reliability and validity, with indicator loadings exceeding recommended thresholds and HTMT values confirming discriminant validity. Structural model analysis reveals that Policy Design, Policy Implementation, and Innovation & Sustainability each have significant positive effects on Sustained Competitive Advantage, collectively explaining 67.3% of its variance. These findings highlight the importance of strategic alignment, effective execution, and continuous innovation in building long-term competitiveness. The study contributes to strategic management literature by providing empirical evidence on how business policy frameworks and innovation-driven practices jointly enhance competitiveness in the manufacturing sector. Practical implications suggest that firms should prioritize coherent policy development, strengthen implementation mechanisms, and integrate sustainability into innovation strategies to achieve durable competitive advantage.